2009
DOI: 10.1080/15374410902851382
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence of ADHD, ODD, Depression, and Anxiety in a Community Sample of 4-Year-Olds

Abstract: Few studies have examined the epidemiology of preschoolers' psychopathology. This study included 796 4-year-old children recruited from schools and pediatric practices in a diverse, urban area. Psychiatric disorder was assessed by a structured interview adapted for preschool children and by questionnaire. The most common disorders were oppositional defiant disorder (ODD) and attention deficit hyperactivity disorder (ADHD). Generalized anxiety disorder (GAD) and depressive disorders were reported in less than 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

21
275
10
10

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 343 publications
(316 citation statements)
references
References 38 publications
21
275
10
10
Order By: Relevance
“…Boys were more likely than girls to evidence externalizing disorders, consistent with some previous epidemiological work, 13,17 including work suggesting that the sex difference in disruptive behavior disorders emerges in early childhood 11 ; others have not observed sex differences in early childhood. 19 The lack of sex differences in internalizing disorders is consistent with studies that show sex differences emerging in adolescence. 56 Sex differences also might be evident in patterns of individual symptom profiles or developmental pathways.…”
Section: Discussionsupporting
confidence: 82%
“…Boys were more likely than girls to evidence externalizing disorders, consistent with some previous epidemiological work, 13,17 including work suggesting that the sex difference in disruptive behavior disorders emerges in early childhood 11 ; others have not observed sex differences in early childhood. 19 The lack of sex differences in internalizing disorders is consistent with studies that show sex differences emerging in adolescence. 56 Sex differences also might be evident in patterns of individual symptom profiles or developmental pathways.…”
Section: Discussionsupporting
confidence: 82%
“…Previous research has shown that, compared with girls, boys more often exhibit ADHD-related behaviors (Gershon & Gershon, 2002;Lavigne, LeBailly, Hopkins, Gouze, & Binns, 2009). Boys also spend more time using media than girls (Rideout, Foehr, & Roberts, 2010) and are more attracted to violent and action-packed media (Cantor, 1998;Olson et al, 2007;Valkenburg & Janssen, 1999).…”
Section: Sex Differencesmentioning
confidence: 99%
“…1,2 Prospective studies indicate that later behavioral and emotional problems begin already in the preschool years. [3][4][5] Available preschool studies report prevalences varying between 7% and 26%, [6][7][8][9][10][11] figures which are comparable to those found among school-aged children, adolescents and adults. 12 The potential long-term effects of treating preschool psychopathology may thus be vast.…”
mentioning
confidence: 94%
“…The prevalence in the present population 11 was in line with Scandinavian findings [22][23][24][25] and fairly low compared to other preschool studies in the US. [6][7][8][9][10] Thus, to increase the generalizability of our results, we will determine screening efficiencies for the most common range of prevalences.…”
mentioning
confidence: 99%